Yinchen Linggui Zhugan decoction ameliorates high fat diet-induced nonalcoholic fatty liver disease by modulation of SIRT1/Nrf2 signaling pathway and gut microbiota - Jiang, Hui; Mao, Tangyou; Sun, Zhongmei; Shi, Lei; Han, Xiao; Zhang, Yang; Zhang, Xiaosi; Wang, Jiali; Hu, Juncong; Zhang, Liming; Li, Junxiang; Han, Haixiao (Frontiers in Microbiology, 2022)
Yinchen linggui zhugan decoction (YLZD) is an effective and classical traditional herbal prescription for treating the nonalcoholic fatty liver disease (NAFLD) and has been proven to be effective in the regulation of lipid metabolism disorder and attenuate inflammation for a NAFLD rat model. However, the exact underlying mechanism has not been elucidated. In the current study, a NAFLD rat model was established using a high-fat diet (HFD) for 10 weeks, followed by YLZD treatment with 1.92 g/kg/day for 4 weeks to explore the mechanisms of YLZD. Our results showed that YLZD decreased the hepatic lipid deposition, restored the liver tissue pathological lesions, inhibited the expression of oxidative stress, and decreased the inflammatory cytokines levels. Meanwhile, the genes and proteins expressions of SIRT1/Nrf2 signaling pathway together with downstream factors including HO-1 and NQO1 were elevated in the YLZD treated NAFLD rats. For further elaborating the upstream mechanism, short-chain fatty acids (SCFAs) in serum and feces were measured by liquid chromatograph mass spectrometer and gas chromatograph mass spectrometer, and the differences in gut microbiota of rats in each group were analyzed through high-throughput sequencing of 16S rRNA. The results demonstrated that the contents of butyric acid (BA) and total SCFAs in YLZD-treated NAFLD rats were significantly increased in serum and feces. 16S rRNA sequencing analysis illustrated that YLZD intervention led to a modification of the gut microbiota composition, with a decrease of Oribacterium, Lactobacillus and the ratio of Firmicutes/Bacteroides, as well as the increase in SCFAs-producing bacteria such as Christensenellaceae, Clostridia, Muribaculaceae, and Prevotellaceae. Spearman rank correlation analysis indicated that BA and total SCFAs were negatively co-related with oxidative stress-related factors and inflammatory cytokines, while they were positively co-related with SIRT1/Nrf2 pathway related genes and proteins. Furthermore, in vitro study confirmed that BA effectively reduced oxidative stress by activating SIRT1/Nrf2 signaling pathway in L02 cells. Together, the present data revealed YLZD could ameliorate HFD-induced NAFLD in rats by the modulation of SIRT1/Nrf2 signaling pathway and gut microbiota.